The Effect of Inner Duct on Aerodynamic Noise of an Outside Rear View Mirror - Zulhazmi, Ammar Naim; Mustaffa, Norrizal (Journal of Automotive Powertrain and Transportation Technology, 2021)
Vehicle outside rear view mirror is one of the parts that produce aerodynamic noise. When the airflow gets contact with the body, aerodynamic noise produced as well as vibration noises caused by friction between air and the body. The study focused on the aerodynamic noise of vehicle outside rear view mirror produced during cruising or speeding. This research aims to analyze sound pressure level reduction by using different design of outside rear view mirror. SOLIDWORKS and ANSYS FLUENT computational fluid dynamics (CFD) simulation were used to design outside rear view mirror and analyze the aerodynamic noise. Boundary condition analysis and 3D modelling geometry were used as the method to conduct this project. This study involved two different outside rear view mirror designs which are the reference design and inner duct design. Each mirror was tested with 3 vehicle speeds: 110 km/h, 130 km/h and 150 km/h. Analysis shows that inner duct outside rear view mirror has lower sound pressure level produced compared to reference outside rear view mirror. An average, inner duct outside rear view mirror has 39.47 % noise reduction while reference outside rear view mirror has lower noise reduction which is 22.03 %. This can be concluded that inner duct outside rear view mirror is better design to reduce air resistance, surface area contacts and sound pressure level.